Simultaneous high-frequency induction heated combustion synthesis and consolidation of nanostructured HfSi2-SiC composite - Park, Jeong-Hwan; Yoon, Jin-Kook; Doh, Jung-Mann; Lee, Byung-Soo; Shon, In-Jin (ELSEVIER SCI LTD, 2009)
Dense nanostructured HfSi2-SiC composite was synthesized by high-frequency induction heated combustion synthesis (HFIHCS) method in one step from powders of mechanically activated HfC and Si. Simultaneous combustion synthesis and densification were accomplished under the combined effects of an induced current and mechanical pressure. Highly dense HfSi2-SiC was produced under simultaneous application of a 60 Mpa pressure and the induced current. The average grain size and mechanical properties (hardness and fracture toughness) of the composite were investigated. (C) 2008 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: ONE-STEP SYNTHESIS; CO HARD MATERIALS; FRACTURE-TOUGHNESS; DENSIFICATION; MOSI2; ZRO2; WSI2; WC